The Impact of Entrepreneurship Education, AI Integration, Microfinance, and Financial Knowledge on Micro, Small, and Medium Enterprises - Nurjannah Nurjannah; Siti Rumenta; Muhammad Arif Rahman (Journal Economic Excellence Ibnu Sina, 2023)
This investigation aims to explore the multifaceted impact of entrepreneurship education, AI integration, microfinance, and financial knowledge on micro, small, and medium enterprises (MSMEs). Employing a qualitative research design, the study utilizes purposive sampling to gather data from a diverse pool of MSME owners and stakeholders. Through thematic analysis, the study examines the interplay between these factors and their implications for MSME growth and sustainability. Preliminary findings suggest that entrepreneurship education fosters innovative thinking, while AI integration enhances operational efficiency. Microfinance serves as a crucial resource for MSMEs' financial needs, complemented by adequate financial knowledge for effective management. The study sheds light on the intricate dynamics shaping the MSME landscape, offering insights for policymakers, educators, and practitioners to bolster MSME development strategies.